Struktur Perasaan dan Dinamika Budaya Digital dalam Film Budi Pekerti: Kajian Cultural Studies Raymond Williams - Meiliana Sirait; Else Liliani; Setyawan Pujiono (Faculty of Languages and Arts, Universitas Negeri Padang, 2026)
The rapid growth of social media has transformed communication practices, social interactions, and the formation of public opinion in contemporary society. Phenomena such as virality, digital shaming, and public judgment have become integral to digital life and are prominently represented in Wregas Bhanuteja’s film Budi Pekerti. This study investigates the representation of the structure of feeling and digital cultural dynamics in the film through Raymond Williams’s Cultural Studies framework. A qualitative approach was employed using cultural textual analysis. The data comprised 40 purposively selected scenes analysed through the concepts of structure of feeling and the categories of dominant, residual, and emergent culture. Data were analysed through data reduction, data display, and conclusion drawing following the model of Miles, Huberman, and Saldaña. The findings reveal that the structure of feeling is the most dominant category (42.5%), encompassing social anxiety, fear of digital stigma, powerlessness, and emotional alienation. Dominant culture is reflected in virality, public judgment, the influence of netizen opinion, and digital social control. Residual culture appears through social ethics, respect for teachers, deliberation, and family solidarity. Emergent culture is represented by digital literacy, critical awareness, digital empathy, mental health awareness, and resistance to cancel culture. The study concludes that Budi Pekerti portrays social media virality as a new form of social power that shapes affective experiences, identity, legitimacy, and social relations in contemporary digital society.